Model Promosi Pariwisata Berbasis Komunitas Kreator: Hubungan Kredibilitas Kreator, Keterlibatan Audiens (Engagement), dan Minat Kunjungan Wisatawan ke Kota Manado - Anggun Therok (JURNAL ILMIAH EDUNOMIKA, 2026)
Abstract This study investigates the relationship between content creator credibility, audience engagement, and tourists’ visit intention in the context of creator community–based tourism promotion in Manado City, Indonesia. Adopting a quantitative, descriptive–explanatory design, data were collected through an online survey of 150 social media users who had consumed tourism-related content about Manado produced by local creators. The instrument employed a five-point Likert scale, and data were analyzed using descriptive statistics and multiple linear regression. The results show that content creator credibility and audience engagement are perceived positively, indicating a favorable assessment of creator-based digital promotion. However, the statistical influence of these variables on visit intention remains limited, suggesting that digital interaction alone is insufficient to generate strong behavioral intention. From a managerial perspective, the findings highlight the need for more structured creator partnership strategies, emphasizing credibility, message consistency, and the integration of digital promotion with practical destination information. The study is limited by its reliance on perceptual data and its focus on a single urban destination. The originality of this research lies in conceptualizing local creator communities as collective promotional actors, providing managerial and policy-relevant insights for developing collaborative, data-driven tourism promotion strategies and strengthening MSME-supported urban tourism ecosystems.